4-aminophenyl sulfone (APS) as novel monomer in fabricating paper based TFC composite for forward osmosis: Selective layer optimization. Issue 2 (April 2020) - Nayak, Vignesh; MS, Jyothi; Balakrishna, R.Geetha; Padaki, Mahesh; Zadorozhnyy, V.Yu; Kaloshkin, S.D.
Graphical abstract: Highlights: The stability of aqueous/organic system over organic/organic system for the formation of surface coating was studied. The work reports potential use of filter paper and novel monomer 4-aminophenyl sulfone for TFC fabrication. The prepared TFC membranes were applied in NaCl and Na2 SO4 rejection via forward osmosis system. m-phenylenediamine monomer showed better film forming properties as compared to 4-aminophenyl sulfone. Abstract: The potential of filter paper as a substrate material and 4-aminophenyl sulfone (APS) as a novel monomer for TFC fabrication is explored for the first time. A novel polyamide selective layer was developed using APS and trimesoyl chloride by interfacial polymerization, whereas the control TFC was prepared by replacing APS with m-phenylenediamine. Formation of the interfacial selective layer was verified by ATR-IR spectra and the stability of the selective surface coatings was discussed by investigating the monomer interaction. Surprisingly, after polymerization, interconnected, cross-linked structure of two monomers was observed. Desalination studies were carried out in FO mode and PRO mode using NH4 HCO3 as a draw solution. Maximum of 90% and 95% rejection was obtained for NaCl and Na2 SO4 salts with a flux of 2.51 and 2.17 LMH respectively. The separation efficiency of the prepared TFC membrane was compared against the likes of a commercial TFC membrane under the same conditions.